Isolation and characterization of spontaneous avirulent variants of Histoplasma capsulatum. - Klimpel, K R (1987)
A selection procedure was developed which allowed us to isolate spontaneous isogenic avirulent clones from virulent strains of Histoplasma capsulatum. The avirulent yeasts had a unique phenotype: they did not aggregate like the parental strains but grew as dispersed budded and unbudded single cells in liquid medium. On solid medium, the avirulent variant strains grew as smooth-textured colonies, whereas the virulent parental strains grew as rough convoluted colonies. Virulence testing in mice demonstrated that the smooth variants gave 50% lethal dose values similar to those of the avirulent Downs strain. Growth curves for the paired rough and smooth strains were similar. Furthermore, they had the same protein profiles when crude cell fractions were separated on one-dimensional polyacrylamide gels or when whole-cell extracts were separated by two-dimensional gel electrophoresis. Electrophoresis of culture supernatants, however, revealed a difference in a released low-molecular-weight peptide that may be related to virulence. In addition to their usefulness in comparative virulence studies, these avirulent strains should prove valuable for H. capsulatum genetic experiments because of the unique ability of these yeasts to grow without clumping.